Experimental Study on the Short-Term Stress Relaxation Response of Chilean Radiata Pine - Saavedra-Flores, E; Garcia-Herrera, C; Yanez-Cart, S; Guzman-Inostroza, C; Pina, J (Springer Science and Business Media Deutschland GmbH, 2022)
In recent years, there has been an increasing interest of engineers and architects in the use of timber in the construction sector. This worldwide trend can be mainly attributed to the reduced environmental impact of building with timber, its high strength-to-weight ratio and its renewable material nature. Nevertheless, in spite of the advantages of building with timber, one of its major disadvantages is its time-dependent structural response. For instance, typical floors and beams made of timber may show decreasing stress levels under constant deformation over time. This phenomenon is known as stress relaxation and can also be affected heavily by environmental factors, such as temperature and moisture changes. This has inevitably led to discourage the use of timber in the construction industry. Due to the relevance of this subject, the present paper addresses the stress relaxation phenomenon in timber specimens subjected to three-point bending loads. In particular, radiata pine species is chosen for this investigation given its popularity as a building material in countries like Australia, Chile, Spain and New Zealand, among others. To investigate experimentally the influence of temperature and relative humidity on the stress relaxation at different deformation states, an environmental chamber was built. The stress relaxation is assessed indirectly by monitoring the relaxation of the load required to maintain the amount of deformation fixed in time inside the environmental test chamber. The experimental results show that within a period of 7 days, the percentage of load relaxation may reach a value of 35% approximately, for a fixed relative humidity of 60% and constant temperature of 27∘C. The present experimental results provide further insight into the time-dependent mechanisms of timber which are still not well-understood, and particularly of those structures made of radiata pine grown in Chile on which only limited experimental data has been reported to date. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.